1998
DOI: 10.1016/s0550-3213(98)00034-0
|View full text |Cite
|
Sign up to set email alerts
|

The BFKL pomeron with running coupling constant: how much of its hard nature survives?

Abstract: We discuss the BFKL equation with a running gauge coupling and identify in its solutions the contributions originating from different transverse momentum scales. We show that for a running coupling constant the distribution of the gluons making up the BFKL Pomeron shifts to smaller transverse momenta so that the dominant part of Pomeron can have a nonperturbative origin. It is demonstrated how this soft physics enters into the BFKL solution through the boundary condition. We consider two kinematical regimes le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…However, this running-coupling GS can also be obtained using the running-coupling version of Eq. (9) [10,11] FIG. 2 (color online).…”
Section: Belowmentioning
confidence: 99%
“…However, this running-coupling GS can also be obtained using the running-coupling version of Eq. (9) [10,11] FIG. 2 (color online).…”
Section: Belowmentioning
confidence: 99%
“…A traditionally delicate point of the small-x resummation is the treatment of the running of the coupling [23][24][25][26][27][28]. While it has been known for some time [29] that running coupling effects can be included perturbatively order by order at small x, in a recent paper [30] we have shown that an all-order resummation of running coupling effects at small x is desirable and can in fact be accomplished.…”
Section: Introductionmentioning
confidence: 99%
“…So, the next-to-leading order (NLO) correction to the BFKL equation is very important, which can be obtained by the resummation of α s [α s ln s] n terms. One may expect to achieve a reasonable intercept with the higherorder corrections at the next-to-leading logarithmic (NLL) accuracy [5][6][7][8][9][10][11][12][13]. The Pomeron intercept has also been analyzed in N = 4 super symmetry theory [14,15].…”
Section: Introductionmentioning
confidence: 99%